Bewertungsmodell zur Evaluation hochauflösender, lichtbasierter Fahrerassistenzsysteme - Jahn, Patric (Spektrum der Lichttechnik, 2020)
Modern headlights are able to project any desired symbol directly onto the street. Feasible applications are driver assistance, information or communication with other traffic participants. Besides all the possibilities the risk of distraction can't be neglected. The present work offers a way to operationalize and quantify this risk. Based on this evaluation a possible homologation can be determined.